Prevalence of Helicobacter Pylori among Dyspeptic Patients - Saeed, Ali Yahya; Pedawi, Safar Mohammad (Sulaimani Journal for Pure and Applied Sciences, 2002)
A total of 150 biopsies were collected from, dyspeptic patients dyspeptic patients with and without ulcers from endoscopic unit of Azadi hospital, Dohuk. This study found a hiqh percentage (64%r) of Helicobacter pylori in the antrum of dyspeptic patients without endoscopic ulcers, while much lower, percentage was found in dyspeptic patients with gastric and duodenal ulcers which was (33%) and (20%) respectively. This low level of percentage was attributed to the inhibitory effect of antibiotics (Metronidazole,'Amoxicillin, Tetracyline) which received by (70%) of patients prior endoscopic examination. Tie study detected a high association (75%) between Helicobacter pylori and patients with chronic active duodenol ulcer Rapid urase test was more reliable tian direct smear for detection of H. pylori, which- can be employed as ascreening test. Helicobacter pylori can be grown anaerobically for at least five days incubation at 37 Co by using selective antibiotics to prevent contamination and without providing gas mixture 85% N2, 10% Co2 and 5% O2 which was used in all previous studies.
Keywords: Helicobacter pylori; Dyspepsia